Upaya Peningkatan Pengetahuan dan Perilaku Hidup Bersih dan Sehat Pada Anak Di Desa Curah Cottok, Kec. Kapongan, Kabupaten Situbondo, Jawa Timur - Ira Ayu Maryuti; Made Indra Ayu Astarini; Kristina Pae; Agustina Chriswinda Bura Mare (LPMP Imperium, 2023)
Cleanliness is the main key to improving health, especially for children. The hands are the part of the body that is first exposed to the external environment, because everything will be touched or held by the hands. This situation is the main gate for germs/viruses/bacteria to enter the body, as well as teeth. So if hand and teeth hygiene cannot be maintained properly, the body will easily be attacked by disease which will disrupt the child's growth and development process. This health education is provided with the aim of helping to increase knowledge and behavior of clean and healthy living in children. The methods used are: lecture, discussion and demonstration. Participants in this activity are school age children in Curah Cottok village, Situbondo.